Reconstruction of maxillary ridge atrophy caused by sequela of dentoalveolar trauma with autogenous bone graft harvested from mentum - Ávila Souza, Francisley; Borrasca, A G; Aranega, Alessandra Marcondes [UNESP]; Ponzoni, Daniela (My University, 2014)
Dentoalveolar traumatisms, particularly those that affect the anterior teeth, interfere adversely in the patient s life.Among them, tooth avulsion is pointed out because it is characterized as a complex injury that affects multiple tissues, andbecause there is no effective treatment available for its resolution with a stable long-term outcome.Aim/Hypothesis: The aim of the present study was to relate a clinical case of complete reconstruction of atrophy of the alveolarbone corresponding to tooth 11, lost by tooth resorption 10 years after the tooth reimplantation procedure.Material and methods: Reconstruction was performed with autogenous bone harvested from the mentum donor site. Surgicalaccess began in the receptor area with a Newman mucoperiosteal incision using a scalpel blade 15 mounted in a scalpel handlefor detachment and exposure of the receptor site. Extensive bone resorption was observed in the vestibular-palatine direction,proved by the thinness of the receptor bed. Decorticalization of the vestibular bone plate was performed. After preparing thereceptor bed, and incision was made in the mucosa in the depth of the anterior vestibular fornix, then a perpendicular muscleperiostealincision to detach and exposure the donor area. The bone graft necessary for reconstruction of the donor area wasdelimited, followed by monocortical osteotomy and the monocortical graft was removed. The next stage was to perform shapingfor passive graft accommodation and fixation by means of two bicortical screws. After fixation of the graft the sharp angles wererounded off in order to avoid possible exposure and/or fenestrations of the reconstructed area, then the receptor and donor areawere sutured. After the 6-month period to allow incorporation of the autogenous graft, an osseointegrated dental implant wasinserted. At the end of the 6-month period of waiting for osseointegration to occur, the process of fabricating the screw-retainedmetal ceramic